2019
DOI: 10.3847/1538-4357/ab2717
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Interstellar Medium and Highly Excited Dense Molecular Gas in the Most Luminous Quasar at z = 6.327

Abstract: Among more than 200 quasars known at z 6, only one object, J0100+2802 (z=6.327), was found hosting a > 10 10 M super-massive black hole (SMBH). In order to investigate the host galaxy properties of J0100+2802, we performed multi-band ALMA observations, aiming at mapping the dust continuum, [C ii] and CO(6-5) emission lines with sub-kiloparsec scale resolution, as well as detecting high-J CO lines in CO(11-10), CO(10-9), and CO(7-6). The galaxy size is measured to be R major = 3.6 ± 0.2 kpc from the high resolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
101
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(113 citation statements)
references
References 66 publications
(92 reference statements)
11
101
1
Order By: Relevance
“…Equation (1) implies that, for instance, a 10 2 M e remnant of a Population III star at z=30 needs to accrete at the Eddington limit for its entire life ( f Duty = 1) to reach a black hole mass >10 9 M e at z∼6, as observed in quasars (e.g., De Rosa et al 2011Mortlock et al 2011;Wu et al 2015;Mazzucchelli et al 2017;Bañados et al 2018;Pons et al 2019;Reed et al 2019;Shen et al 2019). In addition, investigations at mm and submm wavelengths also revealed that the host galaxies of these first quasars are vigorously growing in mass, with star formation rates   -M SFR 100 yr 1 (e.g., Walter et al 2009;Venemans et al 2012Venemans et al , 2016Venemans et al , 2018Wang et al 2013Wang et al , 2019aWillott et al 2015Willott et al , 2017Decarli et al 2018;Kim & Im 2019;Shao et al 2019;Yang et al 2019a).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Equation (1) implies that, for instance, a 10 2 M e remnant of a Population III star at z=30 needs to accrete at the Eddington limit for its entire life ( f Duty = 1) to reach a black hole mass >10 9 M e at z∼6, as observed in quasars (e.g., De Rosa et al 2011Mortlock et al 2011;Wu et al 2015;Mazzucchelli et al 2017;Bañados et al 2018;Pons et al 2019;Reed et al 2019;Shen et al 2019). In addition, investigations at mm and submm wavelengths also revealed that the host galaxies of these first quasars are vigorously growing in mass, with star formation rates   -M SFR 100 yr 1 (e.g., Walter et al 2009;Venemans et al 2012Venemans et al , 2016Venemans et al , 2018Wang et al 2013Wang et al , 2019aWillott et al 2015Willott et al , 2017Decarli et al 2018;Kim & Im 2019;Shao et al 2019;Yang et al 2019a).…”
Section: Introductionmentioning
confidence: 85%
“…mass of only ∼1.9×10 11 M e (Wang et al 2019a). Given this high luminosity, its proximity zone appears to be small [ = R p ( )  7.12 0.13 pMpc], implying that this quasar is relatively young, with a quasar age of t QSO ∼10 5 yr (Eilers et al 2017;Davies et al 2019b).…”
Section: J0100+2802-withmentioning
confidence: 99%
“…For z∼2-4 submillimeter-selected galaxies (SMGs; Blain et al 2002), the measured dust-continuum emission appears 2-4 timesmore compact than the CO emission (Hodge et al 2015;Simpson et al 2015;Chen et al 2017;Calistro Rivera et al 2018). Similarly, for quasar host galaxies at z6 (studied with lower-resolution observations), the dust-continuum sizes also appear z∼2-4 times more compact than those of the CO (Feruglio et al 2018;Wang et al 2019). The dust-continuum and rest-frame optical (but not CO) sizes have also been compared in detail for SMGs (Hodge et al 2016(Hodge et al , 2019Gullberg et al 2019;Lang et al 2019); six massive and compact star-forming galaxies at z∼2.5 (Barro et al 2016); a z∼1.25 starburst (Nelson et al 2019); and massive, Hαselected galaxies at z∼2.2-2.5 (Tadaki et al 2017a).…”
Section: Introductionmentioning
confidence: 95%
“…( 24), assuming that the locally observed scaling relations can be applied to high redshift galaxies. 6 compiled in [46,122] with the mass estimated using the virial method. The gray points are a more complete set of 196 quasars at z 6 compiled in [19], with the mass estimated indirectly from UV luminosity.…”
Section: B Predictions For High Redshift Quasarsmentioning
confidence: 99%
“…[123]. Observations [122,123,125] indicate that the host galaxies of massive, luminous quasars at z 6 have halo dynamical masses and velocity dispersions at least an order of magnitude lower than expected from the local M BH − M bulge and M BH − σ * v relations. However, as shown in Fig.…”
Section: B Predictions For High Redshift Quasarsmentioning
confidence: 99%